The valuation of equities and the GDP growth effect: A global empirical study - Sebastián A. Rey (International Journal of Financial Studies, 2016)
One of the main characteristics of the (recently proposed) non-arbitrage valuation of equities framework is the reduction in pricing subjectivity. This is evidenced in terms of the dividends discount rate and the outlook of future performance (dividends projection) of the company that is being valued. Under this framework, as in the case of derivatives pricing, the discount rate is the risk-free interest rate (not the cost of equity), and the subjectively-determined drift of the stochastic process that drives the operating profits of the company is eliminated. The challenge that emerges is that the structure of the new drift of the operating profits process is undetermined under the methodology (this is a similar feature that is observed in the case of derivatives related to non-tradable assets). This paper proposes that the structure of this new drift is represented by the (country-specific) GDP nominal growth effect. This proposition is tested through an empirical study that involves several companies of 10 equity indices worldwide, for two different periods (1995-2004 and 2005-2014). The results of the test are reasonably successful, meaning that further research related to the framework could provide useful information for the understanding of financial assets and their links to the macro-economy.
Keywords: G1; G12; 330; non-arbitrage valuation; equities pricing; market price of earnings risk; macro-finance linkages